2013
DOI: 10.1080/17405629.2013.765797
|View full text |Cite
|
Sign up to set email alerts
|

Situational moral adjustment and the happy victimizer

Abstract: In this study we examine the possibility that the happy victimizer phenomenon (HVP), which is generally thought to be restricted to a specific period in middle childhood, also appears among adults. In contrast to other studies that explain the HVP as a lack of moral motivation or an insufficiently developed moral self, we propose to explain HVP in terms of a specific moral stage, i.e., a specific kind of moral reasoning. In particular we identify HV-typical moral reasoning with a subform of Kohlberg Stage 2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…From an ethical and economic point of view, we should be much more attentive to the different moral regimes (in terms of moral principles and specific rules for playing various 'cooperation games') that we have at our disposal and how we use them efficiently and intelligently. This is my vision of situation-specific morality (Minnameier, 2012(Minnameier, , 2013(Minnameier, , 2014Minnameier & Schmidt, 2013). It is about establishing appropriate kinds of morality where possible and adapting to (restrictive) situational constraints where necessary.…”
Section: Resultsmentioning
confidence: 98%
“…From an ethical and economic point of view, we should be much more attentive to the different moral regimes (in terms of moral principles and specific rules for playing various 'cooperation games') that we have at our disposal and how we use them efficiently and intelligently. This is my vision of situation-specific morality (Minnameier, 2012(Minnameier, , 2013(Minnameier, , 2014Minnameier & Schmidt, 2013). It is about establishing appropriate kinds of morality where possible and adapting to (restrictive) situational constraints where necessary.…”
Section: Resultsmentioning
confidence: 98%
“…What we know, however, is that HVP has turned out to be salient even among young adults and contrary to the classical explanation, according to which HVP should vanish in late childhood (Nunner-Winkler 2007;Krettenauer, Malti & Sokol, 2008;Minnameier & Schmidt, 2013;Heinrichs et al 2015). Beyond the narrow frame of research on HVP, there is also huge evidence for happy-go-lucky cheating and other forms of moral victimisation among adults (Batson et al, 1999;Ariely, 2012, Rustichini, & Villeval, 2014.…”
Section: Introductionmentioning
confidence: 79%
“…Within this economic body of research, however, it has never been asked how people actually take their decisions and what is really appropriate in specific circumstances. After all, we know that people use moral principles in a situation-specific manner (Krebs & Denton, 2005;Rai & Fiske, 2011;Minnameier, Beck, Heinrichs, & Parche-Kawik, 1999;Minnameier & Schmidt, 2013). Hence, the question arises how economists and non-economists actually take their decisions and what is (more or less) appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…As the rate of people displaying this 'Happy Victimizer Phenomenon' decreases in later age groups (from eight years onwards), it was assumed that this pattern is caused by the absence of a link between cognition and emotion, and therefore might be overcome during later stages of moral development (Krettenauer, Malti, & Sokol, 2008;Nunner-Winkler, 1993). However, further studies revealed that such patterns also emerged to a considerable extent in adolescence (Döring, 2013;Heinrichs et al, this issue) and even in adulthood (Heinrichs et al, 2015;Nunner-Winkler, 2007;Minnameier, Heinrichs, & Kirschbaum, 2016;Minnameier & Schmidt, 2013).…”
Section: Happy Victimising In Adulthoodmentioning
confidence: 92%
“…Research on moral psychology shows that agents simultaneously know about moral rules and attribute positive emotions in cases of transgression. This pattern of ethical decision-making, here called 'happy victimising', was initially detected among children approximately four years old; however, recent research has shown that this pattern also emerges among adolescents and adults (e.g., Heinrichs, Gutzwiller-Helfenfinger, Latzko, Minnameier, & Döring, this issue;Heinrichs, Minnameier, Latzko & Gutzwiller-Helfenfinger, 2015;Nunner-Winkler, 2007;Minnameier, Heinrichs, & Kirschbaum, 2016;Minnameier & Schmidt, 2013). Furthermore, there is evidence of different manifestations of ethical decision-making and emotion attributions, such as the patterns of • 'happy victimizing' (HV; transgressing moral rules, attributing positive emotions),…”
Section: Introductionmentioning
confidence: 99%